Optimization, tolerance analysis and implementation of a Stokes polarimeter based on the conical refraction phenomenon - Peinado, Alba (2015)
Recently, we introduced the basic concepts behind a new polarimeter device based on conical refraction (CR), which presents several appealing features compared to standard polarimeters. To name some of them, CR polarimeters retrieve the polarization state of an input light beam with a snapshot measurement, allow for substantially enhancing the data redundancy without increasing the measuring time, and avoid instrumental errors owing to rotating elements or phase-to-voltage calibration typical from dynamic devices. In this article, we present a comprehensive study of the optimization, robustness and parameters tolerance of CR based polarimeters. In addition, a particular CR based polarimetric architecture is experimentally implemented, and some concerns and recommendations are provided. Finally, the implemented polarimeter is experimentally tested by measuring different states of polarization, including fully and partially polarized light.